Final results of the phase III URO-BCG 4 multicenter study: efficacy and tolerance of one-third dose BCG maintenance in nonmuscle invasive bladder cancer. Issue 3 (March 2017) - Nouhaud, François X.; Rigaud, Jérome; Saint, Fabien; Colombel, Marc; Irani, Jacques; Soulie, Michel; Pfister, Christian
Abstract : The objective of this study was to assess at 3 years bacillus Calmette–Guerin (BCG) maintenance treatment for NMIBC using one-third dose schedule and fewer instillations every 3 or 6 months. This was a phase III randomized study including patients with intermediate-risk or high-risk NMIBC, who received, after a full-dose induction schedule, three-weekly instillations of one-third dose BCG every 6 months (group I) and two-weekly instillations every 3 months (group II) during 3 years. We assessed oncological efficacy, BCG side effects, leukocyturia, and prostate-specific antigen. No tumor recurrence was reported at 36 months for 55 (82.09%) patients in group I versus 64 (90.14%) patients in group II ( P =0.241). Muscle invasion was observed in six patients at 36 months ( P =0.942). In terms of BCG toxicity, grade II and III local or systemic side effects were, respectively, reported in 8.7 and 23.9% of patients during the first year. Nevertheless, the adverse events (AEs) score at 36 months underlined a lower median value of 0.8 in group I versus 1.1 in group II ( P =0.037). Furthermore, 9.9% major AEs occurred in group II versus 3% in group I ( P =0.031). Leukocyturia and prostate-specific antigen level were not associated significantly with either tumor recurrence or muscle progression. We observed a significant difference in the AEs score at 36 months, suggesting less toxicity in patients who were treated with one-third dose of BCG for 3 consecutive weeks every 6 months.